2006
DOI: 10.1128/jvi.80.8.3994-4004.2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N-Linked Glycosylation of Porcine Reproductive and Respiratory Syndrome Virus GP5 on Virus Infectivity, Antigenicity, and Ability To Induce Neutralizing Antibodies

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) glycoprotein 5 (GP5) is the most abundant envelope glycoprotein and a major inducer of neutralizing antibodies in vivo. Three putative N-linked glycosylation sites (N34, N44, and N51) are located on the GP5 ectodomain, where a major neutralization epitope also exists. To determine which of these putative sites are used for glycosylation and the role of the glycan moieties in the neutralizing antibody response, we generated a panel of GP5 mutants conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
229
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(249 citation statements)
references
References 52 publications
18
229
1
1
Order By: Relevance
“…PRRSV-neutralizing antibody titers in serum samples were determined using fluorescent focus neutralization (FFN) as described previously (2,17,43). Briefly, serum samples were heat inactivated for 30 min at 56°C and 2-fold diluted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PRRSV-neutralizing antibody titers in serum samples were determined using fluorescent focus neutralization (FFN) as described previously (2,17,43). Briefly, serum samples were heat inactivated for 30 min at 56°C and 2-fold diluted.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the N-glycan might also be employed by the virus to shield against the neutralizing antibodies (2, 17). Viruses carrying an N-linked glycosylation site mutation at N35 or N51 in GP5 were more sensitive to neutralization by antibodies (2,43). The influence of the N44-linked glycan of GP5 on host immune response remains elusive.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the significance of viral envelope protein glycosylation in virus replication, pathogenesis, and virulence in the natural host is unknown. Recently it has been shown that glycosylation of porcine respiratory and reproductive syndrome virus GP5 affects virus infectivity, antigenicity, and ability to induce neu-tralizing antibodies in swine (2). Loss of N-linked glycosylation from the hemagglutinin-neuraminidase (HN) protein from Newcastle disease virus (NDV), a bird pathogen, results in attenuation of the virus in chickens (25).…”
mentioning
confidence: 99%